Autocontrole de placa com escova e fio dental realizado por indivíduos treinados: 6 meses de acompanhamento - Reiniger, Ana Paula Pereira (2021)
This thesis aimed to answer, through two scientific articles, questions regarding the prevention and treatment of gingival inflammation through self-control of plaque in two patient profiles. The first article aimed to assess whether individuals without prior attachment loss who underwent intensive oral hygiene (OH) training (8 weekly sessions) (a) would be able to maintain the new OH habits for 180 days without professional intervention and ( b) whether dental floss would remain resulting in additional benefits to brushing during this period. Seventy-five subjects with a minimum of 15% proximal sites with gingival bleeding were randomized to receive toothbrush (TB) or toothbrush+dental floss (TB+) training. Then, the individuals were followed for 180 days without professional intervention. Proximal Gingival Index (GI) score 2 (gingival bleeding) was the primary outcome. Comparison between groups was assessed by Mixed Linear Models (p < 0.05). Forty-eight subjects completed follow-up. After reduction of gingival inflammation associated with the training period, no change in gingival condition was observed within the groups for 180 days, showing that the subjects maintained the learned oral hygiene habits. At 180 days, the adjunct use of dental floss (12.8±2.5) showed additional benefits to the toothbrush (19.8±2.2) considering statistically significant differences in proximal gingival bleeding. When patients with intact papillae are trained to properly dental floss, the dental floss associated with the toothbrush promotes a greater reduction in proximal gingival inflammation when compared to the toothbrush. The second article evaluated, in individuals with a history of periodontitis included in periodontal maintenance with a maximum of 7.5% of sites with a GI score of 2, the correlation between plaque accumulation and gingival condition. Forty-two individuals were randomized to perform OH at daily (12h and 24h) or extended (48h) intervals. Plaque Index (PI), GI and Bleeding on Probing (BoP) were measured at baseline, 30 and 90 days. Descriptive statistics and Spearman correlation between plaque accumulation and gingival condition were presented. Both groups, G12/24h and G48h, showed a significant increase in plaque scores throughout the study, but only individuals with extended OH intervals had increased gingival inflammation (BoP and IG score 2). At 90 days, G48h had statistically higher gingival inflammation scores than G12/24h. While the correlations between PI/GI were not affected by the different OH intervals, the correlations between PI/BoP and PI/GI score 2 remained unchanged in G12/24h and increased in G48h. This means that individuals taking OH at extended intervals allow enough plaque development to result in gingival inflammation; while daily OH, although it may result in increased plaque scores, does not allow the development of the same to a condition that induces gingival inflammatory response.